Myeloid-associated differentiation marker is associated with type 2 asthma and is upregulated by human rhinovirus infection - Tanyaratsrisakul, Sasipa; Dy, Alane Blythe C.; Polverino, Francesca; Numata, Mari; Ledford, Julie G. (Frontiers in Immunology, 2023)
Background Human rhinoviruses are known to predispose infants to asthma development during childhood and are often associated with exacerbations in asthma patients. MYADM epithelial expression has been shown to associate with asthma severity. The goal of this study was to determine if MYADM expression patterns were altered in asthma and/or rhinovirus infection and if increased MYADM expression is associated with increased asthma-associated factors. Methods Utilizing H1HeLa cells and differentiated primary human airway epithelial cells (AECs), we measured the expression of MYADM and inflammatory genes by qRT-PCR in the presence or absence of RV-1B infection or poly I:C treatment and with siRNA knockdown of MYADM. Expression of MYADM in the asthmatic lung was determined in the ovalbumin (ova)-challenged murine model. Results MYADM expression was upregulated in the lungs from ova-treated mice and in particular on the subsurface vesicle membrane in airway epithelial cells. Upon infection with RV-1B, human AECs grown at an air–liquid interface had increased the MYADM expression predominantly detected in ciliated cells. We found that the presence of MYADM was required for expression of several inflammatory genes both in a resting state and after RV-1B or poly I:C treatments. Conclusions Our studies show that in a mouse model of asthma and during RV-1B infection of primary human AECs, increased MYADM expression is observed. In the mouse model of asthma, MYADM expression was predominantly on the luminal side of airway epithelial cells. Additionally, MYADM expression was strongly associated with increases in inflammatory genes, which may contribute to more severe asthma and RV-linked asthma exacerbations.